A new dissorophoid temnospondyl from the Allegheny Group (late Carboniferous) of Five Points, Mahoning County, Ohio (USA). (May 2021) - Schoch, Rainer R.; Henrici, Amy C.; Hook, Robert W.
Abstract: A small temnospondyl skull from the upper Carboniferous Allegheny Group of Five Points, Ohio, is referred to a new dissorophoid, Palodromeus bairdi n. gen n. sp. The complete skull with mandibles is preserved in counterparts. It is characterized by, (1) elongated slit-like choana; (2) postfrontal, postorbital, and supratemporal bearing a distinct ridge; and (3) reduced parietal only two-thirds the length of the frontal. Phylogenetic analysis confirms a dichotomy between amphibamiforms and olsoniforms and places Palodromeus bairdi n. gen. n. sp. at the base of the olsoniforms, revealing an early stage in the evolution of that clade. UUID: http://zoobank.org/3871e443-7888-4439-a7c1-9463bc4d87ab